Chronic Non-infectious Uveitis in Patients with Juvenile Idiopathic Arthritis. (3rd July 2016) - Kolomeyer, Anton M.; Tu, Yufei; Miserocchi, Elisabetta; Ranjan, Mangala; Davidow, Amy; Chu, David S.
ABSTRACT: Purpose : To describe clinical findings and analyze treatment evolution of chronic, non-infectious uveitis in patients with juvenile idiopathic arthritis (JIA). Methods : A total of 82 patients (147 eyes) with JIA-related uveitis treated for ≥2 months were included (78% females; 79% bilateral uveitis; 74% anterior uveitis). Outcome measures were visual acuity (VA), inflammation control, side-effects, and surgical procedures. Results : Mean ± SD age at diagnosis was 4.9 ± 3.8 years; mean ± SD follow-up time was 8.7 ± 7.8 years. Mean VA did not significantly change throughout the study. Three (2%) eyes resulted in no light perception (NLP) vision. Thirty (37%) patients underwent 69 procedures. In total, 41 (50%) patients achieved inflammation control. TNF-α inhibitors were significantly associated with inflammation control. Seven (8.5%) patients stopped treatment due to side-effects. Conclusions : JIA is a cause of significant ocular morbidity. TNF-α inhibitor use was associated with inflammation control. Prospective, randomized, double blind clinical trials in this regard are warranted.